GIS-based land suitability evaluation and multi-criteria decision analysis for sustainable enset (Ensete ventricosum (Welw.) Cheesman) cultivation in Hadiya Zone, Central Ethiopia - Alemu Ersino Ersado; Venkata Krishna Talluri (PLoS ONE, 2026)
Land suitability analysis is a key approach for evaluating the potential of land resources for specific uses and for supporting sustainable agricultural planning. In Ethiopia, where agriculture forms the backbone of rural livelihoods, identifying suitable land for staple crops is essential to ensure food security and long-term productivity. This study evaluated the actual land suitability for enset (Ensete ventricosum) cultivation in the Hadiya Zone, Central Ethiopia, by systematically comparing the spatial distribution of key environmental factors with established enset crop requirement standards. For each parameter, spatial data were overlaid with enset-specific ecological thresholds derived from relevant literature and expert consultation. Based on the FAO land evaluation framework, all factors were classified into five suitability classes: Very Highly Suitable (S1), Highly Suitable (S2), Moderately Suitable (S3), Marginally Suitable (N1), and Permanently Not Suitable (N2), enabling the identification of spatial variability in enset suitability and supporting subsequent multi-criteria evaluation and weighted overlay analysis. The analysis evaluated criteria such as soil properties (type, depth, organic carbon content, pH, and texture), topographic situation (slope and elevation), climate variables (rainfall and temperature), and LULC. The integrated analysis revealed that enset cultivation is highly favorable across most of the study area, with 57.72% classified as highly suitable (S1), 36.89% as moderately suitable (S2), 0.16% as marginally suitable (S3), and 5.23% as currently not suitable (N1), while no areas were identified as permanently unsuitable (N2). Overall, the results highlight the strong natural potential of the Hadiya Zone for enset cultivation, although localized constraints related to soil fertility, water availability, and slope conditions may require targeted management interventions.